Nine hydrophobic side chains are key determinants of the thermodynamic stability and oligomerization status of tumour suppressor p53 tetramerization domain. - Mateu, M G (1998)
The contribution of almost each amino acid side chain to the thermodynamic stability of the tetramerization domain (residues 326-353) of human p53 has been quantitated using 25 mutants with single-residue truncations to alanine (or glycine). Truncation of either Leu344 or Leu348 buried at the tetramer interface, but not of any other residue, led to the formation of dimers of moderate stability (8-9 kcal/mol of dimer) instead of tetramers. One-third of the substitutions were moderately destabilizing (<3.9 kcal/mol of tetramer). Truncations of Arg333, Asn345 or Glu349 involved in intermonomer hydrogen bonds, Ala347 at the tetramer interface or Thr329 were more destabilizing (4.1-5.7 kcal/mol). Strongly destabilizing (8.8- 11.7 kcal/mol) substitutions included those of Met340 at the tetramer interface and Phe328, Arg337 and Phe338 involved peripherally in the hydrophobic core. Truncation of any of the three residues involved centrally in the hydrophobic core of each primary dimer either prevented folding (Ile332) or allowed folding only at high protein concentration or low temperature (Leu330 and Phe341). Nine hydrophobic residues per monomer constitute critical determinants for the stability and oligomerization status of this p53 domain.